2017
DOI: 10.1021/jacs.6b11748
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization, Assembly, and Toxicity of Trimers Derived from Aβ

Abstract: Oligomers of the β-amyloid peptide Aβ have emerged as important contributors to neurodegeneration in Alzheimer’s disease. Mounting evidence suggests that Aβ trimers and higher-order oligomers derived from trimers have special significance in the early stages of Alzheimer’s disease. Elucidating the structures of these trimers and higher-order oligomers is paramount for understanding their role in neurodegeneration. This paper describes the design, synthesis, X-ray crystallographic structures, and biophysical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 52 publications
7
90
0
Order By: Relevance
“…We recently demonstrated that stabilizing the trimer formed by peptide 1 through covalent cross-linking allows solution-phase assembly to form higher-order oligomers, such as hexamers and dodecamers. 28 The study presented here demonstrates that hydrophobic interactions between monomers that are not covalently cross-linked can stabilize higher-order oligomers in the same fashion. This finding is significant, because it shows that suitably folded β-hairpin peptides containing amyloidogenic sequences can form stable oligomers.…”
Section: Summary and Conclusionmentioning
confidence: 64%
“…We recently demonstrated that stabilizing the trimer formed by peptide 1 through covalent cross-linking allows solution-phase assembly to form higher-order oligomers, such as hexamers and dodecamers. 28 The study presented here demonstrates that hydrophobic interactions between monomers that are not covalently cross-linked can stabilize higher-order oligomers in the same fashion. This finding is significant, because it shows that suitably folded β-hairpin peptides containing amyloidogenic sequences can form stable oligomers.…”
Section: Summary and Conclusionmentioning
confidence: 64%
“…Extracellular deposits of Aβ peptides in Alzheimer’s are the main pathological events in AD [ 31 , 32 , 33 , 34 ]. Senile plaques or amyloid plaques mainly consist of small amyloid beta-peptides (Aβ) (up to 42 or 43 amino acids long) [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The deposition of β-amyloid peptide (Aβ) in the brain is one of the pathology hallmarks of AD (Citron, 2010 ; Buendia et al, 2016 ; Sepulcre et al, 2016 ; Kreutzer et al, 2017 ). Although high concentrations of endogenous copper (Cu) (Pal et al, 2015 ; Greenough et al, 2016 ; Xu et al, 2016 ), zinc (Zn) (Kulikova et al, 2015 ; Mezentsev et al, 2016 ), and iron (Fe) (Guo et al, 2015 ; Peters et al, 2015 ; Sands et al, 2016 ; James et al, 2017 ) have been found in these amyloidal plaques, the association of those metal ions with Aβ accumulation has not been well established.…”
Section: Introductionmentioning
confidence: 99%